2007
DOI: 10.22605/rrh692
|View full text |Cite
|
Sign up to set email alerts
|

Is walking barefoot a risk factor for diabetic foot disease in developing countries?

Abstract: Is walking barefoot a risk factor for diabetic foot disease in developing countries?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 9 publications
3
25
1
Order By: Relevance
“…We also found that wearing slippers as opposed to sandals and covered shoes increases the risk of foot ulceration about 3-4 times. This is supported by a previous finding suggesting the use of appropriate footwear and wearing them indoors as well as outdoors to prevent foot ulcers [22]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also found that wearing slippers as opposed to sandals and covered shoes increases the risk of foot ulceration about 3-4 times. This is supported by a previous finding suggesting the use of appropriate footwear and wearing them indoors as well as outdoors to prevent foot ulcers [22]. …”
Section: Discussionsupporting
confidence: 83%
“…However, none of these studies have shown these as predictors of foot ulcers, as diabetic ulcer disease seems to have a complicated aetiology, to which a number of structural, pathophysiological, behavioral and environmental factors contribute [19]. Longer duration of diabetes and poor level of education [8], prolonged hyperglycemia [20], inappropriate footwear [21], walking barefoot [22], weak pedal pulses [23], skin changes of the foot [21], presence of callus [24], Charcot deformity [25] and reduced ankle mobility [26] are some of the other common factors documented.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the results should be interpreted with caution, because Muslims wash their feet and toes at least five times a day for their prayers. In this study, few patients had indoor and outdoor barefoot-walking habits, though these patients were much fewer compared to other studies reported elsewhere 45,46. Of these patients, the majority had poor knowledge and did not get advice from their physicians.…”
Section: Discussioncontrasting
confidence: 58%
“…From the 71 included studies, 24 studies evaluated the association of specific variables with DFU development (Table ), 14 studies with DFU recurrence or re‐ulceration (Table ), 15 studies with active or recently healed DFU (Table ), 8 studies with active or past DFU history (Table ) and 10 studies with DFU history (Table ).…”
Section: Resultsmentioning
confidence: 99%